2007
DOI: 10.1016/j.juro.2007.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Distal Urethral Reconstruction of the Glans for Penile Carcinoma: Results of a Novel Technique at 1-Year of Followup

Abstract: Reconstructive glanuloplasty with distal urethra in penile tumor surgery is an innovative, easy and rapid surgical technique with appreciable functional and esthetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 19 publications
0
22
1
1
Order By: Relevance
“…On the other hand, the negative impact of the erectile function can be explained by the penile shortening as demonstrated by our study, leading to difficult vaginal penetration, and the strong psychological consequences of the glans removal. Our results are in contrast with the study by Gulino and colleagues, 23 which reported no differences in postoperative IIEF score, ejaculation or orgasm activity in a series of 14 patients undergoing glansectomy with urethral glanduloplasty.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the negative impact of the erectile function can be explained by the penile shortening as demonstrated by our study, leading to difficult vaginal penetration, and the strong psychological consequences of the glans removal. Our results are in contrast with the study by Gulino and colleagues, 23 which reported no differences in postoperative IIEF score, ejaculation or orgasm activity in a series of 14 patients undergoing glansectomy with urethral glanduloplasty.…”
Section: Discussioncontrasting
confidence: 99%
“…Organ-sparing surgery preserves penile length and shape, with satisfying recovery of the sexual function and acceptable psychological repercussions, while not jeopardizing oncological safety. 14,23 Even the recent update of EAU guidelines underlined the need of as much organ preservation as possible, while removing the primary penile lesion. 12 As an alternative to radical approaches, several surgeons have employed techniques of glansectomy without glans reconstruction with acceptable aesthetic results.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging results were described by Romero et al 23. and Gulino et al 24. In the study by D’Ancona's group,25 who used the Overall Sexual Functioning Questionnaire (OSFQ), nearly 36% of patients had no sexual function or moderately to severely reduced sexual function.…”
Section: Discussionmentioning
confidence: 91%
“…The most common procedure for PSS is glansectomy, which was first described in 1996 [22]. The recurrence rates for glansectomy are less than 4%, with excellent oncologic outcomes [2324252627]. Philippou et al [28] demonstrated that the rates of local recurrence and 5-year CSS after penile-sparing surgery were 8.9% and 91.7%, respectively, during a mean follow-up of 26 months.…”
Section: Discussionmentioning
confidence: 99%